THE INFLUENCE OF COURSE REVIEW HORRAY LEARNING MODEL AND INDEPENDENT LEARNING ON MATHEMATICS LEARNING OUTCOMES OF STUDENTS IN CLASS V SD NEGERI 163080 TEBING TINGGI - Fahmi Chairurozika Lubis; Edy Surya; Asih Menanti (SENSEI RESEARCH CENTER, 2023)
This study aims to determine the effect of applying the Course Review Horay learning model on mathematical learning outcomes based on the learning independence of fifth grade students at SDN 103080 Tebing Tinggi. This research is a Quasi-Experimental research and the design used is Factorial Experimental. The population in this study were all fifth grade students at SDN 103080 Tebing Tinggi. The sample in this study was the VA class as the experimental class and the VB class as the control class. The sampling technique used in this research is Cluster Random Sampling. The instruments used were descriptive tests to measure mathematical learning outcomes and questionnaires to measure student learning independence. Data analysis techniques were carried out using the ???? test for all hypotheses. Based on the ???? tests carried out for hypotheses 1, 2 and 3, it was obtained ???? count > ???? table, meaning that ???? 1 was accepted. So it can be concluded that there is a difference between the experimental class which learns using the Course Review Horay model and the control class which learns using conventional learning. The average score in the experimental class is better than the average score in the control class. Whereas for hypothesis 4, it is obtained ???? count ? ???? table, meaning that ???? 1 is rejected. So it can be concluded that there is no difference between the experimental class that learns using the Course Review Horay model and the control class that learns using conventional learning. With the same average score for the experimental class and the control class. The results of this study can be used by teachers to improve the quality of learning in class.